The Face Mask Waste Recycling Generated During Covid-19 Pandemic In Indonesia - Hamdani, Ahmad Helman; Haryanto, Agus Didit (Journal of Geological Sciences and Applied Geology, 2021)
In Indonesia, the COVID-19 disease has developed rapidly as found on April 20, 2021, there were 1,614,849 positive cases of Covid-19. The increase in cases of the coronavirus has resulted in an increase in the amount of medical waste during the Covid-19. The most common medical waste is face masks, both from hospitals and households. This increase in medical waste will cause environmental damage or health problems.  "A viable solution for reducing the impact of face mask waste on health and the environment is to recycle the face mask mechanically, chemically, and thermally. The proximate, ultimate, FTIR analysis and hardness testing have been carried out to obtain the potential for recycled products. The test results show that carbon ( C ) and volatile matter  (VM)are found in large quantities; polypropylene content is a detected type of plastic. Thus, recycled products can generate potential as a source of renewable energy, cement replacement materials, pipes, packaging materials.. Besides being able to produce new products, this process can also eliminate viruses.